Star-disc interaction in galactic nuclei: formation of a central stellar disc - Panamarev, Taras; Shukirgaliyev, Bekdaulet; Berczik, Peter; Just, Andreas; Spurzem, Rainer (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. We perform high-resolution direct N-body simulations to study the effect of an accretion disc on stellar dynamics in an active galactic nucleus (AGN)